Relationship between teacher appraisal of classroom resources and demands and job satisfaction : implications for administrative support for early childhood educators - DEL CASTILLO, JAN ROCHELLE S. (Archīum Ateneo, 2019)
This study used a correlational quantitative method of research. Pearson correlation was used to determine the relationship of: appraisal of demands and resources and job satisfaction of the same group of participants, which are the early childhood educators. After categorizing the early childhood educators based on their appraisal, it was found out that 75% were resourced, 2.5% was balanced, while 22.5% were stressed. The overall mean raw score for the job satisfaction facets indicates that the teachers have an average satisfaction level. Classroom resources and job satisfaction have a strong, positive, and statistically significant correlation. Classroom demands and job satisfaction show a weak, negative and statistically significant correlation. Based on the findings of this study, it can be concluded that teachers appraisal of classroom resources and classroom demands is related to job satisfaction. The more classroom resources provided, the higher is the level of job satisfaction. The more classroom demands, the lower is the level of job satisfaction.